The Effectiveness of Social Skills Training in Improving Students' Interpersonal Communication - Rafida Rafida; Budi Astuti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
The prevalent issue of low social skills and interpersonal communication among adolescents increases vulnerability to violence, such as bullying, both within the school environment and in social circles. Therefore, this research aimed to measure the effectiveness of social skills training (SST) in improving students' interpersonal communication skills. A quantitative experimental method was adopted, using the Quasi-Experimental Design in the form of a Nonequivalent Control Group Design. Students from grade VIII Madrasah Tsanawiyah (MTs) Negeri 3 Bantul were selected as respondents through purposive sampling and were analyzed using paired sample t-tests. The pre-test and post-test results showed significant improvements in students' interpersonal communication skills in the experimental group, whereas no such improvements were observed in the control group. In conclusion, SST effectively improved interpersonal communication skills of students at MTs Negeri 3 Bantul.